Pengaruh Pendekatan Realistic Mathematics Education (RME) Berbasis Etnomatematika Untuk Meningkatkan Minat Belajar Siswa di Kelas IV SDN 106190 Kota Pari - Lutfiah Az Zahra; Ahmad Landong (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to determine the effect of the Realistic Mathematics Education (RME) approach based on ethnomathematics in increasing students' learning interest. This research uses a quantitative design with a quasi-experimental approach, utilizing pre-test and post-test for both the experimental and control classes. The population and sample of this study were all fourth-grade students of SD Negeri 106190 Kota Pari, consisting of Class IVA as the control class with 18 students and Class IVB as the experimental class with 17 students. The research instrument was tested on 30 students at SD Negeri 106190 Kota Pari. The research instrument used was a pre-test and post-test sheet. Based on the N-Gain score of the experimental class, which was 0.67 and categorized as moderate, it indicated a fairly good improvement in understanding and learning interest. Meanwhile, the control class obtained a negative N-Gain of 0.05, showing no improvement and even a decline. The t-test results showed tcount = 9.65 > ttable = 1.69, which means there is a significant difference between students who learned using the ethnomathematics-based RME approach and those who learned using direct learning models.